Transference theorem and geometric max-stable random variables - Aksomaitis, Algimantas (Lietuvos matematikos rinkinys, 2003)
Transference theorems for logistic and generalized logistic random variables and comparison of direct calculations are given. These rezults specify the rezults of [1].